La práctica de valores y el proceso deficiente de socialización, en los niños de primer año, paralelo “A”, del Centro de Educación Básica “11 de Noviembre” de la ciudad de Riobamba, provincia de Chimborazo año lectivo 2014-2015 - Robalino Álvarez, Mariela Alexandra (2016)
This research was conducted in the first year class "A" from the center of Basic Education "11 de Noviembre" of the city of Riobamba, province of Chimborazo, in order to instill values such as respect, honesty, punctuality, tolerance, patience, love, generosity, including for children who are deficient socialization, so this research paper found some drawbacks of isolation among classmates. As the fundamental basis of this work the reference framework where the problem was established was determined, the formulation of the problem, objectives, and justification, to identify scientific foundations, theoretical theme, and operationalization of variables, developed the framework methodological in which inductive and deductive scientific methods, the descriptive-explanatory research type, research design was the field and not experimental were applied, and the type of study was cross-sectional, consequently the population of 34 children was determined and 1 professor, emphasizing technique, survey and observation, the instruments the questionnaire and the observation guide was applied, and then make a statistical analysis of the results obtained that were obtained from the place of the facts, they showed the conclusions and recommendations based mainly on the problem, to finally make an alternative proposal by an activity guide that helped to strengthen the practice of values and socializing with children of this school, after having applied our proposal in the group students, found that children started favorably close socializing with each other, it emphasized that 5% of the population has difficulty to interact with peers, this being a value that does not affect most infants.